A model of litter harvesting by the Western Australian wheatbelt termite, Drepanotermes tamminensis (Hill), with particular reference to nutrient dynamics - Park, H.; Orsini, J.; Majer, Jonathan; Hobbs, R. (1996)
A series of papers have been published which describe the influence of vegetation and soil type on the Western Australian wheatbelt termite, Drepanotermes tamminensis (Hill), and also on its litter harvesting levels and contribution to the soil nutrient budget. This paper integrates these findings by means of a computer simulation model. The model consists of three modules which respectively describe the dynamics of litter on the ground, the dynamics of litter within termite mounds and how these in turn influence nutrient loads within the habitat. The outputs of the model suggest that this litter harvesting termite plays an important role in the nutrient dynamics of the area and it provides an estimate of the unmeasured variable, litter consumed in mounds by termites, which is consistent with measurements for other termite species with similar feeding habits.